Oceanographic research for a future tourist marina on the Romanian Black Sea coast - Radulescu, Cristiana-Corina (Technium EcoGeoMarine, 2023)
The aim of this paper is to analyze the importance of oceanographic research in the development of a future touristic marina on the Black Sea coast. Oceanographic research plays a crucial role in understanding the marine ecosystem, assessing the impact of human activities, and developing appropriate conservation and management strategies for sustainable tourism. Key areas of research include water quality assessment, biodiversity study, monitoring the impact of tourist activities on marine habitats, studying climate change, and developing adaption and mitigation strategies. By integrating oceanographic research into the planning and development process, stakeholders can ensure responsible and sustainable tourism that protects the marine environment and its biodiversity.